Comparison of Comfort and Effectiveness of Total Face Mask and Oronasal Mask in Noninvasive Positive Pressure Ventilation in Patients with Acute Respiratory Failure: A Clinical Trial. (8th February 2017) - Sadeghi, Somayeh; Fakharian, Atefeh; Nasri, Peiman; Kiani, Arda
Abstract : Background . There is a growing controversy about the use of oronasal masks (ONM) or total facemask (TFM) in noninvasive positive pressure ventilation (NPPV), so we designed a trial to compare the uses of these two masks in terms of effectiveness and comfort. Methods . Between February and November 2014, a total of 48 patients with respiratory failure were studied. Patients were randomized to receive NPPV via ONM or TFM. Data were recorded at 60 minutes and six and 24 hours after intervention. Patient comfort was assessed using a questionnaire. Data were analyzed using t -test and chi-square test. Repeated measures ANOVA and Mann–Whitney U test were used to compare clinical and laboratory data. Results . There were no differences in venous blood gas (VBG) values between the two groups (P > 0.05 ). However, at six hours, TFM was much more effective in reducing the partial pressure of carbon dioxide (PCO2) (P = 0.04 ). Patient comfort and acceptance were statistically similar in both groups (P > 0.05 ). Total time of NPPV was also similar in the two groups (P > 0.05 ). Conclusions . TFM was superior to ONM in acute phase of respiratory failure but not once the patients were out of acute phase.